Client Preparation Techniques: Educating Nonclients about the Process of Personal Counselling - Singer, Joan M.; Stake, Jayne E. (Canadian Journal of Counselling and Psychotherapy, 2012)
Past research indicates that the client preparation technique has improved clients' attitudes, attendance, and outcome in personal counselling. In the present study, this technique was adapted for 40 female and 70 male nonclient college stu- dents. Following the procedure, subjects' self-evaluated knowledge, positive attitudes, and knowledge of psychotherapy increased (p< .0001 ). Most of the gains were main- tained at a one month follow-up. Lower SFS subjects had significantly lower know- ledge scores than middle SFS subjects initially (p< .01), but no significant difference occurred at posttesting or follow-up. These findings suggest that the client prepara- tion technique can be adapted for nonclient groups and may be particularly useful for lower SES groups.